PENYULUHAN MASYARAKAT PEMANFAATAN LIMBAH PLASTIK MENJADI BARANG YANG BERNILAI EKONOMI BAGI IBU-IBU DI DESA PEMATANG SETRAK KECAMATAN TELUK MENGKUDU - Yuliana, Yayuk (Aksara Public, 2019)
The age development that spurred the improvement of Science and Technology (IPTEK) made mayasrakat inevitably to follow the situation, where the satisfying goods needs were dwindling but public consumption continued to increase. The more you increase your satisfaction needs, the more garbage. The garbage is between plastic bottles. Plastic bottles are one of the waste which is quite dangerous because not all plastic bottles can decompose. Plastic bottles can be found anywhere, especially around the community. The bottles are wasted even though they can still be empowered and can even be an additional income for the community if they are able to process them as well as possible. The community service activity (PKM) is expected to be able to improve the quality of the community in processing waste or plastic waste into an economic value item so that it can increase income and support community income in the village of Pematang Setrak, Teluk Mengkudu District, Serdang Bedagai Regency.